THE ROLE OF TECHNOLOGY IN ADVANCING SPORT EDUCATION (American Journal of Interdisciplinary Research and Development, 2023)
This article delves into the transformative influence of technology on the field of Sport Education. As technology continues to evolve, it plays an increasingly vital role in reshaping the landscape of physical education. This article investigates how technology, ranging from virtual reality training to wearable fitness trackers, enhances the practice of Sport Education. It explores how technology-driven innovations are revolutionizing skill development, facilitating global connectivity, and providing students with unprecedented access to sports science knowledge. The research emphasizes the potential benefits and challenges of integrating technology into Sport Education and the implications for the future of physical education.